PEMETAAN PENERAPAN PENGELOLAAN KEUANGAN UMKM SEKTOR PARIWISATA KAB. PANGANDARAN - Nurillah Jamil Achmawati Novel; Suryanto (POLITEKNIK LP3I JAKARTA, 2024)
This research discusses mapping the implementation of financial management in Micro, Small and Medium Enterprises (MSMEs) in the tourism sector in Cintakarya Village, Pangandaran Regency. This research aims to map financial management practices, with a focus on the implementation of non-cash payments (QRIS), financial recording, and investor needs. The research method used was qualitative with in-depth interviews and direct observation of 31 MSMEs. The results show that only one MSME has implemented QRIS, while the majority of MSMEs have not carried out regular financial records and still use manual methods. Some MSMEs also expressed the need for investors, even though there were limitations in business development capacity. Of the MSMEs involved, 64.5% expressed their willingness to participate in assistance in three main areas: investment applications, non-cash payments and financial recording. In conclusion, comprehensive assistance is needed to increase financial literacy and implement digital technology in managing the finances of MSMEs in the tourism sector, to support the growth and sustainability of their businesses in the future.